ANALISIS DAN PERANCANGAN CLUSTERING SISWA BARU MENGGUNAKAN METODE K-MEANS PADA SMK NEGERI 1 KOTA JAMBI - Tandy, Juliana; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2019)
Every year there will be students who continue education to the next stage, including at SMK Negeri 1 Kota Jambi, Event admission of new students is done every 1 year, in the selection process and reception requires the application of more efficient is to use the application, change the system Manual into the system computerized and perform a new grouping students by majors at SMK Negeri 1 Kota Jambi namely Computer Engineering and Networks, Accounting, Office Administration and Marketing. Therefore Final report with the title " Analysis and design of Clustering New Students Using the K-Means Method at SMK Negeri 1 Kota Jambi ". The purpose of writing this thesis report is to determine the new admissions system and a new grouping students by majors at SMK Negeri 1 Kota Jambi. In writing this report require student data, the data value of national examination results, majors available, and student admission quotas. The results obtained by the registrant data reports, reports on the screening of new students by quotas, and the results of grouping students who have been in the selection. Results be obtained as a function of weight for admission of new students each school year and make an efficient work system for the school.